Flerspråklig ungdom og familien: Språklige praksiser, aktørskap og identiteter - Johnsen, Ragni Vik (UiT Norges arktiske universitet, 2021)
The aim of this thesis is to contribute with knowledge on multilingual adolescents’ language practices, agencies and identity construction in the family. The families have in common that they have adolescent children, that one parent have emigrated from a Latin-American country and that they live in the same Northern-Norwegian city. The data is collected through a methodological triangulation and consists of self-recordings in three families (ca. 15 hours), semi-structured interviews (12 individual and group interviews) and language portrait drawings (cf. Busch 2015) with the parents and the adolescents. The thesis examines how the adolescents relate to their own multilingualism and how they make use of multilingual resources to achieve their communicative goals. The thesis shows how the adolescents use multilingual resources to challenge linguistic and social regimes, demonstrate belonging to the family and to tease each other. Moreover, the thesis shows how they, through creative and playful linguistic practices, challenge and (re)negotiate linguistic and social norms. The analyses demonstrate different ways in which the adolescents exert agencies, for example by claiming authority, show resistance and subvert linguistic and social hierarchies. The results complement previous sociolinguistic research on adolescents, language and identities by contributing with knowledge about multilingual adolescents’ linguistic practices and identity constructions in families. Furthermore, it contributes empirically and methodologically to research on multilingual families by investigating adolescents’ perspectives and by employing interactional sociolinguistics. Målet med denne avhandlinga er å bidra med kunnskap om flerspråklige ungdommers språklige praksiser, aktørskap og identitetskonstruksjon i familien. Datamaterialet er samla inn gjennom metodisk triangulering, og består av egenopptak i tre familier (ca. 15 timer opptak), semi-strukturerte intervjuer (12 individuelle- og gruppeintervjuer), samt språkportretter (jf. Busch 2015) med både foreldrene og ungdommene. Familiene har til felles at barna er i tenårene, at minst én av foreldrene har flyttet til Norge fra et latinamerikansk land, og at de bor i samme nordnorske by. Avhandlinga undersøker hvordan ungdommene forholder seg til egen flerspråklighet og hvordan de utnytter flerspråklige ressurser for å nå kommunikative mål. Avhandlinga viser blant annet at ungdommene tar i bruk ulike språk for å utfordre språklige og sosiale regimer, vise tilhørighet til familien og for å erte hverandre. I tillegg viser avhandlinga hvordan familiemedlemmene gjennom kreative praksiser og leken språkbruk utfordrer og (re)forhandler språklige og sosiale normer. Analysene viser også ulike måter ungdommene utøver aktørskap på, ved for eksempel å innta autoritetsposisjoner, utøve motstand og ved å bekrefte eller snu om på språklige og sosiale hierarkier. Resultatene i avhandlinga komplementerer tidligere sosiolingvistisk forskning på ungdom, språk og identitet ved å bidra med kunnskap om flerspråklige ungdommers språklige praksiser og identitetskonstruksjoner i familien. Videre bidrar avhandlinga empirisk og metodisk til forskning på flerspråklige familier ved å studere ungdommers perspektiver og språklige praksiser, og ved å benytte interaksjonelle, sosiolingvistiske metoder. Esta tesis investiga las prácticas lingüísticas, la agencia y la construcción de la identidad en adolescentes multilingües en el contexto de la familia. Todas las familias tienen en común que al menos uno de los padres ha emigrado a Noruega desde un país latinoamericano, cuyos hijos son adolescentes y viven en la misma ciudad en el Norte de Noruega. Se emplea una triple metodología, ya que se combinan grabaciones (circa 15 horas), entrevistas semiestructuradas (12 individuales y en grupo), y retratos lingüísticos (Busch 2015) dibujados por los padres e hijos en tres familias distintas. Asimismo, esta tesis investiga las experiencias y perspectivas sobre el multilingüismo de los adolescentes y cómo utilizan lenguas diferentes para lograr sus objetivos comunicativos, documentando cómo los adolescentes utilizan recursos multilingües para desafiar regímenes sociales y lingüísticos, para demostrar pertenencia a la comunidad familiar, y para manifestar burlas. Además, esta tesis documenta cómo los adolescentes utilizan sus repertorios lingüísticos de forma lúdica y creativa en interacciones familiares para desafiar y (re)negociar normas lingüísticas y sociales en la familia por medio de tales prácticas. Los análisis que se presentan aquí demuestran también cómo los adolescentes dan muestras de agencia social y lingüística al reclamar posiciones de autoridad o resistencia y al subvertir jerarquías lingüísticas y sociales. Los resultados complementan las investigaciones previas sobre adolescentes, lenguaje e identidad, ya que contribuye con nuevas perspectivas a nuestra comprensión de las practicas lingüísticas y la construcción de las identidades de adolescentes multilingües. Centrándose en los adolescentes y empleando métodos basados en la sociolingüística interaccional, esta tesis también aporta contribuciones empíricas y metodológicas al estudio de las familias multilingües.